The vasodilation effects of curcumin and its derivatives on isolated aortic of rats - Agung Endro Nugroho; Djoko Suhardjono; Mulyono .; Supardjan A. Margono (Indonesian Journal of Pharmacy, 2008)
Hypertension is a disease which need a complex therapy and high cost of drugs. This fact urge exploration of new antihypertensive drug. The aim of the research was to asses to look at the activity of curcumin and its derivatives bisdemethoxy curcumin and bis(demethoxydehydroxy) curcumin on the contraction of isolated organ smooth muscle induced by an α1-adrenergic receptor agonist (phenylephrine), and to assay relaxation effect on this organ. In this study, aortic organ represented a vascular system. This research was conducted using an isolated organ technique with isotonic transducer. The results have shown that curcumin and its analogs bisdemethoxy curcumin and bis(demethoxydehydroxy) curcumin could inhibit the contraction of isolated organ smooth muscle, and showed relaxation effects of this organ. The inhibitory effect on the isolated organ might be mediated by non-competitive antagonism mechanism on a1-adrenergic receptor, whereas the relaxation effects were suggested through nitric oxide (NO) independent pathway.Key words : curcumin, isolated organ, vasodilation, relaxation